Coaching Clinic Model Passing Sepak Bola pada Anak Sekolah Dasar - Ruslan, Ruslan; Podungge, Risna; Mile, Sarjan; Syam, Asry (Universitas Negeri Gorontalo, 2024)
Football is a popular sport that has many benefits, both physically, mentally, and socially. One of the basic skills in football is passing, which plays an important role in teamwork and the quality of the game. However, limited facilities, coaches, and structured training programs often hinder elementary school students in Indonesia from developing this skill. This community service activity aims to improve the passing ability of elementary school students through the